Where are the poor and where are the trees?: targeting of poverty reduction and forest conservation in Vietnam (Vietnamese) - Muller, D.; Epprecht, M.; Sunderlin, William D. (Center for International Forestry Research, 2006)
This paper highlights the spatial linkages of forest quality with poverty incidence and poverty density in Vietnam. Most of the Vietnamese poor live in densely populated river deltas and cities while remote upland areas have the highest poverty incidences, gaps, and severities. Forests of high local and global value are located in areas where relatively few poor people live, but where the incidence, gap, and severity of poverty are strongest, and where the livelihood strategies are based on agricultural and forest activities. Analysis was conducted combining country-wide spatial data on commune-level poverty estimates and the geographic distribution of forest quality. The results suggest the usefulness of targeting investments in remote areas that combine poverty reduction and environmental sustainability.